Path-Independent All-Visible Orthogonal Photoswitching for Applications in Multi-Photochromic Polymers and Molecular Computing - Köttner, Laura; Dube, Henry (Angewandte Chemie International Edition, 2024)
Synthetic molecular photoswitches have taken center stage as high-precision tools to introduce light-responsiveness at the smallest scales. Today they are found in all areas of applied chemistry, covering materials research, chemical biology, catalysis, or nanotechnology. For a next step of applicability truly orthogonal photoswitching is highly desirable but to date such independent addressability of different photoswitches remains highly challenging. Herein we present the first example of all-visible, all-light responsive, and path- independent orthogonal photoswitching. By combining two recently developed indigoid photoswitches - peri-anthracenethioindigo and a rhodanine-based chromophore - a four-state system is established and each state can be accessed in high yields completely independently and also with visible light irradiation only. The four states give rise to four different colors, which can be transferred to a solid polymer matrix to yield a versatile multi-state photochromic material. Further, combination with a fluorescent dye as a third component is possible, demonstrating the applicability of this orthogonal photoswitching system in all-photonic molecular logic behavior and information processing.
CRIS-Team Scopus Importer:2024-11-01
Keywords: molecular logic; multi-photochromism; orthogonal photoswitching; peri-anthracenethioindigo; rhodanine